Psychometric properties of the Persian version of the Questionnaire of Cognitive Schema Activation in Sexual Context (QCSASC) in unsuccessful sexual situations - Abdolmanafi, A.; Winter, Sam; Ghorban Jahromi, R.; Farahani, H.; Peixoto, M.; Nobre, P. (Brunner - Routledge, 2017)
The aim of this study was to translate and adapt to Persian, and to assess psychometric properties of the Questionnaire of Cognitive Schema Activation in Sexual Context (QCSASC). A total of 265 Iranian participants (121 women and 144 men) were recruited for this study. A principal component analysis (PCA) with varimax rotation and subsequent confirmatory factor analysis revealed a best fitting five-factor structure similar to the original QCSASC: Incompetence, Undesirability, Abandon/Rejection, Powerless/Helpless, and Difference. However, in the Iranian sample, the original Self-Depreciation dimension was included in the Incompetence and Undesirability factors. An Abandon/Rejection dimension was also evident, and may be explained by cultural, social, and religious factors in the Iranian culture. Additionally, reliability analysis has supported the internal consistency (adequate Cronbach's alpha values) and temporal stability (test–retest reliability) of the QCSASC in an Iranian sample. The findings suggest the adequacy of the Persian version of the QCSASC to assess cognitive schemas in sexual context among Iranian men and women.